PERBAIKAN DAN PERKUATAN STRUKTUR PADA BANGUNAN CAGAR BUDAYA - Nusantoro, Agung (Konstruksia, 2012)
Indonesia represent one of the region which is gristle to earthquake disaster. Damage earthquke event generate loss through physical and also non physical. This physical damage and losses also affect at cultural pledge building which spread over in Indonesia. Hence require to strive strength and repair at the culture pledge building so that building history value can be defended. Cultural pledge building in this study is limited at the building made from brick wall. Effort strength and report in this study conducted at building element like sloof, wall, column, ring balk and roof. We expected with effort this strength and repair, cultural pledge building structure become strongerly than before.Kata Kunci: Perbaikan, Perkuatan, Bangunan, Cagar Budaya